Positive electrode slurry containing PVDF (Polyvinylidene Fluoride) and preparation method thereof

By reacting an additive containing -N=C=O group in the positive electrode slurry of lithium battery with a PVDF binder to form macromolecules, the problem of difficulty in taking into account both the bonding performance and stability in the prior art is solved, and lithium is improved The adhesion and flexibility of the battery pole sheet enhance the safety and electrochemical stability of the battery.

CN119252916APending Publication Date: 2025-01-03ZHEJIANG LANTIAN ENVIRONMENTAL PROTECTION HI TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310804050.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing lithium battery positive electrode slurry is difficult to take into account both the improvement of bonding performance and stability, which leads to the battery being prone to bumps, short circuits and spontaneous combustion problems. The commonly used modification methods have safety risks and electrochemical instability problems.

Method used

Add additives containing at least 2 -N=C=O groups to the positive electrode slurry to form macromolecules by reacting with end groups of PVDF binder to improve bonding performance and flexibility while maintaining the stability of the slurry .

Benefits of technology

Without affecting the stability of the slurry, the bonding and flexibility of the PVDF adhesive is significantly improved, the pressure and heat resistance of the electrode sheet are enhanced, and the internal resistance and heating risks of the battery are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004317142640000101
    Figure BDA0004317142640000101
  • Figure FDA0004317142630000011
    Figure FDA0004317142630000011
  • Figure FDA0004317142630000012
    Figure FDA0004317142630000012
Patent Text Reader

Abstract

The invention discloses a positive electrode slurry containing PVDF and a preparation method thereof, the positive electrode slurry comprises a PVDF binder, a positive electrode active material and an additive, the additive contains at least two-N = C = O groups, the use amount of the additive is 20-300ppm of the mass of the PVDF binder, and the use amount of the additive is 20-300ppm of the mass of the PVDF binder. The-N = C = O group contained in the additive reacts with the end group of the PVDF binder at a high temperature to be bonded together, so that a chain extension effect is generated, and the molecular chain length of the PVDF binder is increased. According to the positive electrode slurry containing PVDF disclosed by the invention, under the condition that the molecular weight of PVDF is not increased, the binding power of PVDF and the flexibility of a pole piece are improved, and the stability of the positive electrode slurry is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a positive electrode slurry containing PVDF and a preparation method thereof, and more particularly to a positive electrode slurry having good PVDF adhesion and good slurry stability obtained by adding a small molecule additive, wherein the prepared pole piece has good flexibility, and the positive electrode slurry is particularly suitable for a lithium iron phosphate system. Background Art

[0002] Lithium batteries are composed of positive electrodes, negative electrodes, separators, and electrolytes. The preparation of positive electrodes usually involves dispersing positive electrode active materials, binders, conductive agents, etc. in solvents such as N-methylpyrrolidone (NMP) through high-speed stirring to form a positive electrode slurry suspension, which is then coated on a current collector and dried in an oven to form a positive electrode current collector.

[0003] In order to improve the bonding performance of the binder, a common solution is to increase the molecular weight of PVDF. However, when the molecular weight of PVDF increases, under the action of intermolecular attraction, the PVDF binder is very likely to adhere to multiple positive electrode active materials and conductive agent particles and carbon black to form agglomerates during the homogenization stage, which reduces the stability of the slurry and even loses fluidity. Slurries with poor stability are prone to form bumps on the pole pieces after coating. After being assembled into a battery, the bumps are easy to puncture the battery separator, causing a short circuit between the positive and negative electrodes and spontaneous combustion of the battery.

[0004] Adhesion performance and slurry stability cannot be achieved at the same time. In order to improve the stable storage time of the slurry, the CN113659145A patent document uses polyvinylidene fluoride as a binder and adds a small amount of polytetrafluoroethylene to the slurry, which can improve the anti-gel ability of the positive electrode slurry and improve the positive electrode compaction density, while reducing the impact on the battery cycle performance. However, the adhesion of polytetrafluoroethylene is weaker than that of polyvinylidene fluoride, and the addition of additional polytetrafluoroethylene reduces the proportion of positive electrode materials, resulting in a decrease in battery capacity. The CN112952092A patent document adds polyacrylonitrile polymers to polyvinylidene fluoride copolymers to improve the anti-gelation ability of the slurry. However, the electrochemical stability of polyacrylonitrile polymers is not as good as that of polyvinylidene fluoride, which is not conducive to lithium batteries maintaining a higher charge and discharge platform. Patent document CN115124686B uses polyurethane to modify PVDF to prepare adhesive for lithium-ion batteries. The polyurethane and PVDF are first mixed and reacted to obtain an adhesive, which is then used as a component to prepare positive electrode slurry. The length of the modified PVDF molecular chain increases, which makes gelation easy to occur during the preparation of the positive electrode slurry. In addition, polyurethane contains a large amount of fatty chains (hydrocarbon chains), which cannot adapt to the harsh electrochemical environment of lithium batteries. Moreover, the fatty chains are not resistant to high temperatures, posing a safety risk. Summary of the invention

[0005] In order to solve the above problems, the present invention unexpectedly found that an additive containing at least 2 -N=C=O groups is added to the positive electrode slurry. During the homogenization process of the positive electrode slurry or the stirring stage after the homogenization, the additive does not react with PVDF, thereby ensuring the stability of the slurry. After the positive electrode slurry is coated on the current collector, in the curing stage (drying and solvent removal stage), the -N=C=O group contained in the additive reacts and bonds with the end group of the PVDF binder to produce a chain extension effect, so that the original independent multiple PVDF molecular chains are bonded into a macromolecule. If there are 2 -N=C=O groups in the additive, a linear super macromolecule is formed. If the -N=C=O group in the additive is greater than 2, a body-shaped cross-linked macromolecule is formed. This macromolecule has a strong intermolecular force, which can greatly improve the bonding performance and flexibility. However, since the reaction does not occur in the homogenization stage, the stability of the slurry is not affected.

[0006] The technical solution of the present invention is as follows:

[0007] The present invention provides a positive electrode slurry containing PVDF, wherein the positive electrode slurry comprises a PVDF binder, a positive electrode active material and an additive.

[0008] The additive contains at least 2 -N=C=O groups,

[0009] The PVDF binder contains terminal groups that can react with -N=C=O groups,

[0010] The dosage of the additive is 20 to 300 ppm of the mass of the PVDF binder.

[0011] The amount of the additive used in the present invention is 20 to 300 ppm of the mass of the PVDF binder. If the amount is too little, the effect is not obvious. If the amount is too much, too much unreacted additive will remain, which is not conducive to the application performance. In terms of improving adhesion and stability, preferably, the amount of the additive is 50 to 200 ppm of the mass of the PVDF binder, and more preferably, the amount of the additive is 83 to 138 ppm of the mass of the PVDF binder.

[0012] The additive of the present invention contains at least two -N=C=O groups, which react with the end groups of the PVDF binder, and the molecular weight of the PVDF binder is increased by more than 2 times, thereby increasing the bonding performance and flexibility.

[0013] The additive of the present invention is a compound containing at least two -N=C=O groups. Preferably, the additive is selected from hexamethylene diisocyanate (HDI), hexamethylene diisocyanate trimer (t-HDI), toluene-2,4-diisocyanate (TDI), toluene-2,4-diisocyanate trimer (t-TDI), 4,4'-methylenebis(phenyl isocyanate) (MDI), 1,3-bis(1-isocyanato-1-methylethyl)benzene (CAS: 2778-42-9), 2,6-diisocyanatotoluene At least one of ester (CAS: 91-08-7), isophorone diisocyanate (IPDI), 4,4′-diisocyanate dicyclohexylmethane (HMDI) or meta-xylylene diisocyanate (XDI); from the perspectives of the matching of the temperature at which the additive reacts with the PVDF end group and the slurry curing temperature, the improvement of the adhesion and the flexibility of the pole piece, and the green, safe and environmentally friendly performance, more preferably, the additive is selected from at least one of hexamethylene diisocyanate (HDI) or hexamethylene diisocyanate trimer (t-HDI).

[0014] The structural formula of the above additives is as follows:

[0015] Hexamethylene diisocyanate (HDI):

[0016] Hexamethylene diisocyanate trimer (t-HDI):

[0017] Toluene-2,4-diisocyanate (TDI):

[0018] Toluene-2,4-diisocyanate trimer (t-TDI):

[0019] 4,4'-Methylenebis(phenyl isocyanate) (MDI):

[0020] 1,3-Bis(1-isocyanato-1-methylethyl)benzene (CAS: 2778-42-9):

[0021] 2,6-Diisocyanatotoluene (CAS: 91-08-7):

[0022] Isophorone diisocyanate (IPDI):

[0023] 4,4′-Dicyclohexylmethane diisocyanate (HMDI):

[0024] Meta-Xylylenediisocyanate (XDI):

[0025] The end groups of the PVDF binder of the present invention are selected from -OH, -SO4 - , -O-CH(CH3)2, -COOH, -OC-(CH3)3, -OOC-O-CH(CH3)2 or -NH2. Preferably, the end groups of the PVDF binder are selected from -OH, Or at least one of -NH2, which makes the reaction between the additive and the PVDF binder easier and more efficient, and no small molecules such as H2O and CO2 are generated during the entire reaction process, which will not affect the slurry construction and does not require modification of the existing coating equipment.

[0026] The content of the above-mentioned end groups in the PVDF binder of the present invention is arbitrary. Preferably, the content of the above-mentioned end groups is 30 to 200 ppm.

[0027] The PVDF binder containing the above-mentioned end groups is obtained by introducing the end groups into the PVDF molecular chain by using the initiator, telogen and monomer containing the above-mentioned end groups in the PVDF polymerization process.

[0028] The initiator of the present invention is at least one selected from diisopropyl peroxydicarbonate, tert-butyl peroxide, bis(tert-butyl peroxide)cyclohexane, di-n-propyl peroxydicarbonate, potassium persulfate, ammonium persulfate or sodium persulfate.

[0029] The telogen of the present invention is selected from at least one of ethyl acetate, diethyl malonate, polyacrylic acid, polyethylene glycol, polyvinyl alcohol, ethylenediamine, isopropanol, ethanol, methanol, ethylene oxide or alkyl sulfate.

[0030] The monomer of the present invention is selected from at least one of acrylic acid, hydroxyethyl acrylate, amino acrylate or glycidyl acrylate.

[0031] The preparation method of the PVDF binder of the present invention adopts a conventional PVDF suspension polymerization method or a PVDF emulsion polymerization method. In order to increase the slurry stability time, preferably, the preparation method of the PVDF binder adopts an emulsion polymerization method.

[0032] The PVDF binder of the present invention can be a homopolymer of VDF, or a copolymer of VDF and other comonomers, wherein the other comonomers are selected from at least one of vinyl fluoride, trifluoroethylene, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, acrylic acid, acrylate, methacrylic acid, methacrylate, maleic acid, maleate, citraconic acid, citraconic acid, vinyl acetate, vinyl carbonate, hydroxyethyl acrylate, amino acrylate or glycidyl acrylate, and the content of the comonomer structural unit accounts for 0.01 to 2 mol% of the total PVDF amount.

[0033] The reaction temperature of the -N=C=O group of the additive of the present invention and the end group of the PVDF binder is 50-130° C. Matchingly, the curing temperature of the positive electrode slurry is controlled within the same range. In order to ensure that the additive fully reacts with PVDF, the curing temperature can be increased or the curing time can be extended.

[0034] When the additive is hexamethylene diisocyanate (HDI) or hexamethylene diisocyanate trimer (t-HDI), the reaction temperature of the additive and the PVDF binder is 70-120°C.

[0035] The relative weight average molecular weight of the PVDF binder of the present invention is the relative weight average molecular weight commonly used in the field of binders. Preferably, the relative weight average molecular weight of the PVDF binder is 600,000 to 1.5 million, preferably 600,000 to 1.3 million.

[0036] The PVDF binder of the present invention has a solution viscosity of 7 wt% NMP solution of 1500-10000 Pa·s, preferably 2000-6000 mPa·s. If the viscosity is below the range, the bonding force is insufficient, cracking or powdering may occur easily, and if the viscosity is above the range, the slurry may easily gel.

[0037] The positive electrode active material described in the present invention is a positive electrode active material that can be used in lithium ion batteries, such as lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium nickel phosphate, lithium iron silicate, lithium ferrous fluorosulfate, lithium iron borate, lithium iron borate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, lithium manganate, lithium nickel manganate, lithium transvanadate, etc.

[0038] The technical solution of the present invention is particularly suitable for positive electrode active materials in powder form, such as lithium iron phosphate. Positive electrode active materials in powder form are more likely to gel and have poor stability during the homogenization process. The technical solution of the present invention avoids the phenomenon of gel and poor stability without reducing the solid content of the slurry.

[0039] The amount of the PVDF binder used in the present invention accounts for 0.5-3wt% of the total amount of the positive electrode slurry. If it is less than 0.5wt%, the bonding force is insufficient, and the pole piece is prone to cracking or powdering. If it is higher than 3wt%, the slurry will gel, the battery internal resistance will be high, or the heat will be severe. Preferably, the amount of the PVDF binder used accounts for 1.0-2.5wt% of the total amount of the positive electrode slurry.

[0040] The present invention also provides a method for preparing a positive electrode slurry containing PVDF, the method comprising the step of adding the additive before, during or after the homogenization process.

[0041] As an implementation mode, when the homogenization process adopts a dry method, after the active material, the conductive agent, and the PVDF are evenly mixed, the solvent and the additive are added, and then stirred for a period of time; the additive can also be added during the dry stirring.

[0042] As another embodiment, when the homogenization process adopts a wet method, the PVDF resin and additives are dissolved in a solvent, and then the positive electrode active material and the conductive agent are added and stirred evenly; or only the PVDF resin can be dissolved first, and then the additives are added together with the active material and the conductive agent and stirred evenly.

[0043] The stirring time of the present invention is based on the dispersion of the additives. Preferably, the stirring time is more than 30 minutes.

[0044] The positive electrode slurry containing PVDF of the present invention maintains a temperature below 50-60° C. in all process stages before coating, ensuring that the PVDF does not react with the additive in all process stages before the curing stage.

[0045] Compared with the prior art, the present invention has the beneficial effect of improving the bonding strength and flexibility of the PVDF binder without changing the solid content of the positive electrode slurry, that is, improving the bonding performance of the PVDF binder without changing the stability of the positive electrode slurry. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.

[0047] The test methods of the embodiments of the present invention and the comparative examples are as follows:

[0048] Relative weight average molecular weight: GPC was used for testing, with N,N-dimethylformamide as the mobile phase, a flow rate of 0.1 ml / min, a test temperature of 50°C, and a narrow distribution polystyrene with a molecular weight of 10,000 to 10,000,000 as the standard sample to draw a standard curve. The relative weight average molecular weight of the obtained vinylidene fluoride polymer is a relative value relative to the molecular weight of polystyrene.

[0049] End group content: calculated by NMR, refer to Macromolecules 46.18 (2013): 7146-7157.

[0050] Preparation of PVDF binder

[0051] 1-PVDF resin A1 containing -OH terminal groups

[0052] Add 1.8L water, 6g paraffin, and an appropriate amount of emulsifier to a 3L high-pressure reactor, evacuate the reactor and replace it with nitrogen three times, heat it to 80°C, then pump in 0.6g ethyl acetate with an auxiliary metering pump, and pump in VDF with a monomer metering pump to reach a pressure of 4.5Mpa. Add 50g of ammonium persulfate solution with a mass concentration of 0.6%, and continuously add VDF to keep the pressure at 4.5Mpa. When the VDF reaction amount reaches the predetermined value, stop adding monomers, and empty the material after the pressure of the reactor drops to 2.0Mpa. After demulsification, washing and drying, PVDF resin A1 is obtained. After measurement, the relative weight average molecular weight is 696292, the molecular weight distribution is 2.32, and the viscosity of the 7wt% solution is: 4500mPa·s; the end group content is 70ppm (NMR test).

[0053] 2-PVDF resin A2 containing -O-CH(CH3)2 end groups

[0054] Add 3.2L water, 10g paraffin, and an appropriate amount of dispersant to a 5L high-pressure reactor, evacuate the reactor and replace with nitrogen three times, heat to 40°C, then pump in 8g ethyl acetate with an additive metering pump, and pump in VDF / HFP with a monomer metering pump to reach a pressure of 6.0Mpa. Add 2.7g of a solution of diisopropyl peroxydicarbonate with a mass concentration of 15%, and continuously add VDF / HFP to keep the pressure at 6.0Mpa. The HFP mass ratio is 0.6%. When the monomer reaction amount reaches the predetermined value, stop adding monomers, and empty the material after the reactor pressure drops to 2.0Mpa. Wash and dry to obtain PVDF resin A2. After measurement, the relative weight average molecular weight is 1319031, the molecular weight distribution is 2.10, and the viscosity of the 7wt% solution is: 2410mPa·s; the end group content is 190ppm.

[0055] 3-PVDF resin A3 containing -COOH end groups

[0056] Add 1.8L water, 6g paraffin, and an appropriate amount of emulsifier to a 3L high-pressure reactor, vacuum the reactor and replace it with nitrogen three times. After the last vacuuming, add 4g HFP, then heat it to 80°C, then pump in 1g ethyl acetate with an auxiliary metering pump, and pump in VDF with a monomer metering pump to reach a pressure of 4.5Mpa. Add 50g of ammonium persulfate solution with a mass concentration of 0.6%, and add an acrylic acid solution with a mass concentration of 0.1% at a rate of 1.5mL / min by a horizontal flow pump until the reaction is completed. Continue to add VDF to keep the pressure at 4.5Mpa. When the VDF reaction amount reaches the predetermined value, stop adding monomers, and empty the reactor after the pressure drops to 2.0Mpa. After demulsification, washing and drying, obtain the resin PVDF resin A3. After measurement, the relative weight average molecular weight is 757762, the molecular weight distribution is 1.91, the solution viscosity of 7wt% is: 3200mPa·s, and the total end group content is 133ppm.

[0057] 4-PVDF resin A4 containing -NH2 end groups

[0058] Add 1.8L water, 6g paraffin, and an appropriate amount of emulsifier to a 3L high-pressure reactor, vacuum the reactor and replace it with nitrogen three times. After the last vacuuming, add 4g HFP, then heat it to 80°C, then pump in 0.2g ethyl acetate with an auxiliary metering pump, and pump in VDF with a monomer metering pump to reach a pressure of 4.5Mpa. Add 50g of ammonium persulfate solution with a mass concentration of 0.6%, and add 0.1% acrylic acid amino ester solution at a rate of 1.0mL / min with a horizontal flow pump until the reaction is completed. Continue to add VDF to keep the pressure at 4.5Mpa. When the VDF reaction amount reaches the predetermined value, stop adding monomers, and empty the reactor after the pressure drops to 2.0Mpa. After demulsification, washing and drying, obtain resin PVDF resin A4. After measurement, the relative weight average molecular weight is 623742, the molecular weight distribution is 2.31, the solution viscosity of 7wt% is: 4140mPa·s, and the end group content is 178ppm.

[0059] 5. Contains End-terminated PVDF resin A5

[0060] Add 1.8L water, 6g paraffin, and an appropriate amount of emulsifier to a 3L high-pressure reactor, evacuate the reactor and replace with nitrogen three times. After the last evacuation, add 4g HFP, then heat to 80°C, and then pump in 0.2g ethyl acetate with an auxiliary metering pump, and pump in VDF with a monomer metering pump to reach a pressure of 4.5Mpa. Add 50g of ammonium persulfate solution with a mass concentration of 0.6%, and add a 0.1% glycidyl acrylate solution with a horizontal flow pump at a rate of 1.0mL / min until the reaction is completed. Continue to add VDF to keep the pressure at 4.5Mpa. When the VDF reaction amount reaches the predetermined value, stop adding monomers, and when the pressure of the reactor drops to 2.0Mpa, empty the material. After demulsification, washing and drying, the resin PVDF resin A5 is obtained. The relative weight average molecular weight was measured to be 660592, the molecular weight distribution was 2.24, the viscosity of the 7wt% solution was 3210 mPa·s, and the end group content was 184 ppm.

[0061] Example 1

[0062] 6 g PVDF resin A1, 190 g lithium iron phosphate, 4 g conductive agent, 135 g NMP solvent, and 20 ppm M1 additive (relative to the mass of PVDF resin A1).

[0063] The lithium iron phosphate, conductive agent and PVDF binder of the above components are mixed evenly by planetary stirring; NMP solvent and M1 additive are added, and stirring is continued to fully mix them to complete the preparation of the positive electrode slurry, and the temperature is controlled not to be higher than 50°C during mixing. M1 is hexamethylene diisocyanate trimer (t-HDI).

[0064] Example 2

[0065] Same as Example 1, except that: 83 ppm of M1 additive (relative to the mass of PVDF resin A1).

[0066] Example 3

[0067] Same as Example 1, except that: 138 ppm of M1 additive (relative to the mass of PVDF resin A1).

[0068] Example 4

[0069] Same as Example 1, except that: 300 ppm of M1 additive (relative to the mass of PVDF resin A1).

[0070] Example 5

[0071] Same as Example 1, except that: 83 ppm of M2 additive (relative to the mass of PVDF resin A1). M2 is hexamethylene diisocyanate (HDI)

[0072] Example 6

[0073] Same as Example 4, except that: 138 ppm of M2 additive (relative to the mass of PVDF resin A1).

[0074] Example 7

[0075] Same as Example 4, except that: 300 ppm of M2 additive (relative to the mass of PVDF resin A1).

[0076] Example 8

[0077] 6 g PVDF resin A2, 190 g lithium iron phosphate, 4 g conductive agent, 135 g NMP solvent and 83 ppm M1 additive (relative to the mass of PVDF resin A2).

[0078] The lithium iron phosphate, conductive agent and PVDF binder with the above-mentioned components are evenly mixed by planetary stirring; NMP solvent and M1 additive are added, and stirring is continued to make them fully mixed to complete the preparation of the positive electrode slurry. The temperature is controlled not to be higher than 50° C. during mixing.

[0079] Example 9

[0080] Same as Example 8, except that: 138 ppm of M1 additive (relative to the mass of PVDF resin A2).

[0081] Example 10

[0082] Same as Example 8, except that: 300 ppm of M1 additive (relative to the mass of PVDF resin A2).

[0083] Embodiment 11

[0084] 6 g PVDF resin A3, 190 g lithium iron phosphate, 4 g conductive agent, 135 g NMP solvent and 83 ppm M1 additive (relative to the mass of PVDF resin A3).

[0085] The lithium iron phosphate, conductive agent and PVDF binder with the above-mentioned components are evenly mixed by planetary stirring; NMP solvent and M1 additive are added, and stirring is continued to make them fully mixed to complete the preparation of the positive electrode slurry. The temperature is controlled not to be higher than 50° C. during mixing.

[0086] Example 12

[0087] Same as Example 11, except that: 138 ppm of M1 additive (relative to the mass of PVDF resin A3).

[0088] Embodiment 13

[0089] Same as Example 11, except that: 300 ppm of M1 additive (relative to the mass of PVDF resin A3).

[0090] Embodiment 14

[0091] 6 g PVDF resin A4, 190 g lithium iron phosphate, 4 g conductive agent, 135 g NMP solvent and 138 ppm M1 additive (relative to the mass of PVDF resin A4).

[0092] The lithium iron phosphate, conductive agent and PVDF binder with the above-mentioned components are evenly mixed by planetary stirring; NMP solvent and M1 additive are added, and stirring is continued to make them fully mixed to complete the preparation of the positive electrode slurry. The temperature is controlled not to be higher than 50° C. during mixing.

[0093] Embodiment 15

[0094] 6 g PVDF resin A5, 190 g lithium iron phosphate, 4 g conductive agent, 135 g NMP solvent and 138 ppm M1 additive (relative to the mass of PVDF resin A5).

[0095] The lithium iron phosphate, conductive agent and PVDF binder with the above-mentioned components are evenly mixed by planetary stirring; NMP solvent and M1 additive are added, and stirring is continued to make them fully mixed to complete the preparation of the positive electrode slurry. The temperature is controlled not to be higher than 50° C. during mixing.

[0096] Comparative Example 1

[0097] 6g PVDF resin A1, 190g lithium iron phosphate, 4g conductive agent, 135g NMP solvent.

[0098] The lithium iron phosphate, conductive agent and PVDF binder with the above-mentioned components are evenly mixed by planetary stirring; NMP solvent is added and stirring is continued to make it fully mixed to complete the preparation of the positive electrode slurry. The temperature is controlled not to be higher than 50° C. during mixing.

[0099] Comparative Example 2

[0100] The same as comparative example 1, except that 6 g of PVDF resin A2 was used.

[0101] Comparative Example 3

[0102] The same as comparative example 1, except that 6 g of PVDF resin A3 was used.

[0103] Comparative Example 4

[0104] The same as comparative example 1, except that 6 g of PVDF resin A4 was used.

[0105] Comparative Example 5

[0106] The same as comparative example 1, except that 6 g of PVDF resin A5 was used.

[0107] Test Case

[0108] (I) Slurry stability

[0109] At room temperature, a small amount of prepared positive electrode slurry was placed in a beaker and allowed to stand completely. The slurry was stirred with a glass rod every hour to observe its flow state and whether agglomerates appeared. When agglomerates that affect natural flow appeared, the time was recorded. This time is the gel time (slurry stability time). According to this method, the stability of the positive electrode slurry was tested. Table 1 shows the stability data of the positive electrode slurry of the embodiment and the comparative example.

[0110] Table 1 Slurry stability data

[0111] Slurry stability time, h Example 1 30 Example 2 30 Example 3 28 Example 4 28 Example 5 30 Example 6 30 Example 7 28 Example 8 18 Example 9 18 Example 10 18 Embodiment 11 15 Example 12 15 Embodiment 13 14 Embodiment 14 15 Embodiment 15 14 Comparative Example 1 30 Comparative Example 2 18 Comparative Example 3 15 Comparative Example 4 15 Comparative Example 5 15

[0112] The data in Table 1 show that: from the stability time of Comparative Example 1 and Comparative Example 3, Comparative Example 4, and Comparative Example 5, it can be seen that the copolymer of VDF and acrylic acid, amino acrylate, and glycidyl acrylate has a shorter slurry stability time than the VDF homopolymer. From the data comparison between Example 1 and Comparative Example 1, Example 8 and Comparative Example 2, Example 11 and Comparative Example 3, Example 14 and Comparative Example 4, and Example 15 and Comparative Example 5, the present invention does not significantly affect the stability of the positive electrode slurry by adding 20 to 300 ppm of additives to the slurry.

[0113] (ii) Adhesion performance and flexibility

[0114] The positive electrode slurry of the embodiment and the comparative example was prepared into a pole piece, and the preparation process was as follows: the positive electrode slurry was prepared at a surface density of 200 g / m 2 The film is coated on the current collector, and the solvent NMP is removed by heating in sections, vacuuming, etc. The heating temperature is 90-120°C.

[0115] The peel strength before compression and the peel strength after compression at 90t, as well as the flexibility of the pole piece were tested. Table 2 shows the bonding performance and flexibility data of the embodiment and the comparative example.

[0116] Table 2 Adhesion performance and flexibility data

[0117]

[0118]

[0119] Note: ①Peel strength test method: refer to GB 2792-2014 peel strength test method.

[0120] ②Flexibility test method: refer to GB / T 1731-2020 Test method for flexibility of paint film and putty film.

[0121] The data in Table 2 show:

[0122] From Example 1 and Comparative Example 1, after adding 20 ppm of the additive, the peel strength before pressing increased by 86%, the peel strength after pressing increased by 15%, and the flexibility was better.

[0123] From Example 3 and Comparative Example 1, after adding 138 ppm of the additive, the peel strength before pressing increased by 202%, the peel strength after pressing increased by 80%, and the flexibility was better.

[0124] From Example 1 to Example 4, when the amount of additives is gradually increased, the peel strength before and after compression are significantly improved. When the amount of additives is increased to a certain content, the increase in the peel strength before and after compression is not obvious. When the amount of additives is within the range of 20 to 300 ppm, the flexibility does not change much.

[0125] From Example 2 and Example 5, compared with HDI, the t-HDI additive improves the pre-pressing peel strength, post-pressing peel strength and flexibility more.

[0126] From Example 3, Example 9, Example 12, Example 14 and Example 15, it can be seen that the end group type and end group content of the PVDF resin have an impact on the peel strength before compression, the peel strength after compression and the flexibility.

[0127] From the peel strength and flexibility of Comparative Examples 1, 3, 4 and 5, it can be seen that the copolymerization of VDF with acrylic acid, amino acrylate and glycidyl acrylate can increase the peel strength of the electrode before and after pressing.

[0128] From the peeling strength and flexibility of Comparative Examples 1 and 2, it can be seen that the pre-pressing peeling strength of the pole piece prepared by the suspension PVDF is lower than that of the emulsion PVDF, and the flexibility of the pole piece prepared by the suspension PVDF is lower than that of the emulsion PVDF.

Claims

1. A positive electrode slurry containing PVDF, the positive electrode slurry comprising a PVDF binder, a positive electrode active material and an additive, characterized in that: The additive contains at least 2 -N=C=O groups, The PVDF binder contains terminal groups that can react with -N=C=O groups, The dosage of the additive is 20 to 300 ppm of the mass of the PVDF binder.

2. The positive electrode slurry containing PVDF according to claim 1, characterized in that: The additive is selected from at least one of hexamethylene diisocyanate, hexamethylene diisocyanate trimer, toluene-2,4-diisocyanate, toluene-2,4-diisocyanate trimer, 4,4'-methylenebis(phenyl isocyanate), 1,3-bis(1-isocyanato-1-methylethyl)benzene, 2,6-toluene diisocyanate, isophorone diisocyanate, 4,4'-diisocyanate dicyclohexylmethane or meta-xylylene diisocyanate.

3. The positive electrode slurry containing PVDF according to claim 1, characterized in that: The PVDF binder contains terminal groups selected from -OH, At least one of -SO4-, -O-CH(CH3)2, -COOH, -OC-(CH3)3, -OOC-O-CH(CH3)2 or -NH2.

4. The positive electrode slurry containing PVDF according to claim 3, characterized in that: The PVDF binder contains terminal groups selected from -OH, Or at least one of -NH2.

5. The positive electrode slurry containing PVDF according to any one of claims 1 to 4, characterized in that: The reaction temperature of the -N=C=O group of the additive and the end group of the PVDF binder is 50-130°C.

6. The positive electrode slurry containing PVDF according to claim 1, characterized in that: The relative weight average molecular weight of the PVDF binder is 600,000 to 1.5 million.

7. The positive electrode slurry containing PVDF according to claim 1, characterized in that: The solution viscosity of the NMP solution containing 7 wt% of the PVDF binder is 1500-10000 mPa.s.

8. The positive electrode slurry containing PVDF according to claim 1, characterized in that: The positive electrode active material is selected from at least one of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide or lithium cobalt oxide.

9. The positive electrode slurry containing PVDF according to claim 1, characterized in that: The PVDF binder is a homopolymer of VDF or a copolymer of VDF and other comonomers. The comonomer is selected from at least one of vinyl fluoride, trifluoroethylene, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, acrylic acid, acrylate, methacrylic acid, methacrylate, maleic acid, maleate, citraconic acid, citraconic acid, vinyl acetate, vinyl carbonate, hydroxyethyl acrylate, amino acrylate or glycidyl acrylate, and the content of the comonomer structural unit accounts for 0.01 to 2 mol% of the total PVDF.

10. A method for preparing a positive electrode slurry containing PVDF according to any one of claims 1 to 9, characterized in that: The preparation method comprises the step of adding the additive before, during or after the homogenization process.